Dietary Lactobacillus fermentum and Lactobacillus paracasei improve the intestinal health of broilers challenged with coccidia and Clostridium perfringens - Li, Peng; Zheng, Liyun; Qi, Ya; Liu, Zhipeng; Du, Encun; Wei, Jintao; Zhang, Zhengfan; Guo, Shuangshuang; Ding, Binying (Frontiers in Veterinary Science, 2022)
Necrotic enteritis (NE) is a great threat to the intestinal health of broilers, which decreases the growth performance and results in significant economic losses. Lactobacillus fermentum (LF) and Lactobacillus paracasei (LP) exerts beneficial effects on the intestinal health. The present study was arranged to investigate the effects of dietary LF and LP on the intestinal health and growth performance of broilers challenged with coccidia and Clostridium perfringens (CCP). The animal trial was carried out using 336 broilers (Rose 308) for the period of 35 days with a completely randomized design. The broilers were divided into 4 treatments, the control (CTR) group fed the basal diet and without CCP challenge, the CCP group fed the basal diet and with CCP challenge. The broilers in the CCP+LF and CCP+LP groups were challenged by CCP, and meanwhile, LF (1× 109 CFU/g) and LP (1× 109 CFU/g) were supplemented into the basal diets, respectively. Results showed that, the growth performance and the intestinal morphology were negatively affected by CCP challenge. In addition, the number of coccidia in the intestinal digesta and the relative abundance of Escherichia coli in the cecal digesta were increased. Besides, the mRNA level of IgA in the jejunum was down-regulated, and the transcript level of IL-8 was up-regulated by CCP challenge. Dietary LF and LP failed to improve the growth performance of broilers with CCP challenge. However, they were beneficial for the intestinal barrier function. In addition, dietary LF was able to alleviate the downregulation of TGF-β mRNA level in the spleen with CCP challenge, and decreased the lesion scores compared with the CCP group. Furthermore, dietary LP alleviated the upregulation of IL-8 mRNA level in the jejunum with CCP challenge, and reduced the number of coccidia in the ileal digesta. In conclusion, dietary LF and LP failed to mitigate the negative effects of CCP infection on growth performance, however they were able to improve the intestinal health of broilers challenged with CCP by strengthening the intestinal barrier and alleviating inflammation.